Model Dialog Transformatif Yesus Dalam Yohanes 1-4 - Antonio, Lucky; Edward Nimits Abraham; Samuel Elkana; Sarah Wassar; Tri Subekti (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
The transformative dialogue model of Jesus in the Gospel of John 1-4 portrays Jesus Christ's consistent evangelistic interaction through dialogues with various figures in different contexts, leading to changes in understanding and spiritual transformation both individually and collectively among those He encountered. This study aims to identify and analyze the transformative dialogue model employed by Jesus Christ in John 1-4 to achieve transformative goals, fostering relationships conducive to faith growth among His listeners and bringing people to faith in Him. The research methodology involves qualitative descriptive and exploratory text analysis with a hermeneutical approach to understanding the cultural and theological contexts underlying each effective mission dialogue. The study analyzes six dialogues in John 1-4 involving Jesus Christ conversing with four different groups of people. Dialogues are communication tools for bringing about deeper spiritual truths and change. The findings illustrate that Jesus Christ used various dialogical strategies to effectively communicate the Gospel message to people from diverse social backgrounds, building relationships that facilitate faith growth. The transformative dialogue model of Jesus Christ in John 1-4 demonstrates wise and open dialogue in evangelism, providing valuable guidance for modern evangelistic practices and emphasizing the need for adaptation to individual social contexts for maximum effectiveness in bringing people to Christ.